Treatment approaches and antibiotic use for emergency dental treatment in Turkey - Kaptan RF; Haznedaroglu F; Basturk FB; Kayahan MB (Dove Medical Press, 2013)
Rabia Figen Kaptan,1 Faruk Haznedaroglu,2 Fatima Betul Basturk,3 Mehmet Baybora Kayahan11Department of Endodontics, Yeditepe University, 2Department of Endodontics, Istanbul University, 3Department of Endodontics, Marmara University, Istanbul, TurkeyAbstract: The purpose of this study was to gather information about Turkish general dental practitioners' treatment approaches towards endodontic emergencies, antibiotic-prescribing habits, and their participation in lifelong learning programs. Questionnaires were given to dentists who attended the 16th National Congress organized by the Turkish Dental Association. From 1,400 questionnaires distributed, 589 (43%) were deemed usable in this study. This survey dealt with questions that were subdivided into two main topics: dental emergency treatment approaches, and antibiotic prescription and information on lifelong learning program participation. The statistical analysis was conducted with a Χ2 test at a significance level of P<0.05. For irreversible pulpitis cases in vital teeth, most of the dental practitioners (65.3%) preferred single-visit root canal treatments. For teeth presenting a periapical lesion, the preferred treatment approach was root canal treatment (91.5%). The rate of prescription of analgesics and antibiotics was 21.7% in untreated acute apical periodontitis cases and 41% in acute apical abscess cases. Frequently prescribed antibiotics were amoxicillin–clavulanate (61.8%) and amoxicillin (46.5%). There was a tendency for practitioners to attend congresses as their years of professional practice increased (P<0.0001). There have been discrepancies between taught and observed practice. Educational initiatives are needed to prevent inappropriate prescription of antibiotics.Keywords: antibiotic prescription, endodontic emergency, survey, Turkey